PENERAPAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS 4 SDN KESONGO 01 KABUPATEN SEMARANG - Riska Puji Rahayuningtyas; Henny Dwi K (ELEMENTARY SCHOOL JOURNAL PGSD FIP UNIMED, 2017)
The study aims to improve the learning outcomes of science students grade 4 SDN Kesongo 01. Research methods undertaken are TOD conducted two cycles per cycle consisting of two meetings. The subjects of this study are 4th grade students of SDN Kesongo 01 with 23 students. The results showed an increase in the learning outcomes of grade 4 students SDN Kesongo 01 lesson 2016/2017. With the increase of students' learning outcomes in cycle I, 17 students got the score according to KKM standard ≥70 (73,9%) and on cycle II 22 students got value according to KKM standard ≥70 (95,7%). Keywords: Contextual Teaching and Learning Approach, Learning                 Outcomes of Science